Feedback information processing between male and female of physical education collage students and its effect on motor learning - Rashid, Amer (Journal of Physical Education, 2008)
Since the female started to participate in the sport events especially in the Olympic games, those who concerned with sport had noticed that the standard of the female sport achievements are much less from the male standard . Thus, the scientists as well as the researchers from a different specialties started to study this phenomena as well as the differences between sex in the sport field . Motor Learning is one of the specialties that has to have contribution in this regard . Thus, the problem of this study is to investigate the ability of male and female to process easy or hard Feedback information . (in the form of knowledge of Result-KR) and how that effect performance , learning and retention of discret motor skill . Total of forty male and female (20each) of physical education college students were chosen as a study sample which was divided into two conditions , easy and hard information processing condition each condition consist of male and female group . Distance positioning task on the linear track way apparatus was chosen as a motor task . Performance test showed that male and female gained almost equal significant improvement for both conditions which reflect their equal abilities to process information . Learning tests with either short or long rest period under the easy processing condition have showed a reversed effect , when male showed improvement while female showed deterioration, but both did not reach the level of significance . Meantime male and female showed improvement under the hard processing condition in which only the male reached the level of significance with short rest period test . Difference scores of the retention tests was a negative value which indicate deterioration and forgetting for all groups specially for female which showed the highest . Movement time (MT) was shorter for female under the two conditions . The study recommended that the sex type almost does not affect differentially on information processing ability and we could think in increasing the skill trials repeation during the teaching seasion when working with females and creating a teaching setting that required a hard information processing